Prevalence and Risk Factors of Type 2 Diabetes Mellitus in the Rural Population of Mangalore, South India - Padmanabha, Usha R; Nalam, Udayakiran; Badiger, Sanjeev; Nagarajaiah, Puneeth (National Journal of Community Medicine, 2017)
Introduction: Non communicable diseases are accountable for demise of 38 million people each year with diabetes accounting 1.5 million of global deaths.India is presently facing the epidemic of diabetes with around 31.7 million cases in 2000 and likely to cross 79.4 million by 2030.The current study was conducted to assess the prevalence and risk factors of type 2 DM among population aged 35 years and above in the rural population of Mangalore. Methods: Present study was a cross sectional study conducted in the rural population among participants aged 35 years and above.Based on the prevalence rate of 16% by Rao et al the total sample was 226.Households were interviewed by using Systematic Random sampling with estimation of RBS using glucometer. Results: Out of 226 subjects, 31.4% were male and 68.6% were female with mean age of 54 +11 yrs.The overall prevalence of diabetes and prediabetes was 28.3% and 11.5%. Hypertension, increased BMI, Waist Hip Ratio, age group of 46-55years and sedentary lifestyle showed a significant association with diabetes.In Multivariate analysis, being normotensive, negative genetic history and normal WHR in male was protective factors against diabetes. Conclusion: The study showed an overall prevalence of Type 2 DM of 28.3%. Hence there is a need for effective primary preventive strategies to reduce the incidence.